(untitled) (Plant Tissue Culture and Biotechnology, 2012)
Multiple shoots of Vanilla planifolia were induced from nodal explants under influence of different concentrations of plant growth regulators and coconut water (CW). A comparison of shoot regeneration between semi solid and liquid culture media was also investigated. Ninety seven per cent of the explants produced a mean number of 9.6 shoots with a mean shoot length of 4.70 cm when cultured on liquid MS supplemented with 1.0 mg/l BAP in combination of 15% CW. Shoots generated were rooted with frequency of 93% on MS supplemented with 1.0 mg/l NAA with a mean number of 2.9 roots per shoot and mean length of 4.0 cm within four weeks. The plantlets were transferred to sand : compost mixture (1 : 2) with 85.0% survival rate recorded after four weeks of acclimation. Key words: Regeneration, coconut water, nodal culture, vanilla D.O.I. 10.3329/ptcb.v21i1.9560 Plant Tissue Cult. & Biotech. 21(1): 27-33, 2011 (June)